2016
DOI: 10.1038/srep36586
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab and Dexamethasone Attenuate the Ductular Reaction in Mice

Abstract: Chronic hepatic injury is accompanied by a ductular response that is strongly correlated with disease severity and progression of fibrosis. To investigate whether anti-inflammatory drugs can modulate the ductular response, we treated mice suffering from a steatotic or cholestatic injury with anti-TNF-α antibodies (Infliximab) or glucocorticoids (Dexamethasone). We discovered that Dexamethasone and Infliximab can both modulate the adaptive remodeling of the biliary architecture that occurs upon liver injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…With respect to HPC activation, the TNF α antagonist Infliximab could inhibit HPC activation and fibrosis in both a mouse model of steatosis and cholestasis. 43 However, while early clinical trials with alcoholic hepatitis patients have shown promising results with the single treatment with Infliximab, 44 , 45 randomised trials using either IFX or Etanercept (soluble TNF receptor) were disappointing. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…With respect to HPC activation, the TNF α antagonist Infliximab could inhibit HPC activation and fibrosis in both a mouse model of steatosis and cholestasis. 43 However, while early clinical trials with alcoholic hepatitis patients have shown promising results with the single treatment with Infliximab, 44 , 45 randomised trials using either IFX or Etanercept (soluble TNF receptor) were disappointing. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Enhanced levels of TNF have also been detected in Mdr2 −/− mice compared to wild-type mice [ 105 ]. A preclinical functional study in the DDC model indicated that anti-TNF treatment had no effect on serum levels of liver enzymes but prevented the ductular reaction as well as extracellular matrix deposition in mouse livers [ 116 ]. We wondered whether TNF would affect liver inflammation, liver damage, and fibrosis in chronic experimental sclerosing cholangitis in the Mdr2 −/− mouse model.…”
Section: Role Of Tnf In Autoimmune Liver Disease (Aild)mentioning
confidence: 99%
“…Observational studies show that estrogen therapy is an important risk factor in gallbladder disease [ 46 , 47 ]. Studies on experimental models also suggested a beneficial effect of GC treatment, such as dexamethasone, for attenuation of ductular impairment [ 48 , 49 ]. Our data from the MDR2KO mouse model, showing cholangiocyte hyperplasia and hepatic fibrosis being more pronounced in females than in males, and being partially reduced by corticosterone treatment, are in agreement with these reports.…”
Section: Discussionmentioning
confidence: 99%